PENGARUH BAURAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MOBIL TOYOTA DI KOTA BANDA ACEH - Fadhilla Maulida (Jurnal Ilmiah Manajemen Muhammadiyah Aceh, 2011)
The purpose of  this study was to determine the effect of the promotion mix of Toyota car purchasing decisions in the city of Banda Aceh. Study sample were as many as 98 other communities in the city of Banda Aceh, which was taken by Ramdom sampling. The data was collected by distributing questionnaires. Further data analysis using statistical tools that multiple linear regression.The results showed that the advertising, sales promotion, personal selling and publicity positive influence on purchase decisions of Toyota cars in the city of Banda aceh.faktor the most dominant influence on purchasing decisions is a personal sales, sales promotion followed in second place. Based on the results whereas the t test (partial) indicates that a partial test of the four independent variables are variables advertising, sales promotion, personal selling and publicity significantly influence the purchasing decisions of Toyota Cars in Banda Aceh.             The conclusion that can be taken from this study is the variable advertising, sales promotion, publicity and personal pennjualan influence on purchasing decisions of Toyota cars in the city of Banda Aceh. The most significant variable is a private sale. Keywords : promotion mix, purchasing decisions, advertising, sales promotions, personal selling and publicity